2017
DOI: 10.5812/jjm.58151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Juglans nigra Green Husk and Clotrimazole on Candida albicans in Rats

Abstract: Background: Black walnut (Juglans nigra) is known to have antimicrobial and antifungal effects in vitro. Objectives: This study aimed to compare the effects of extracts derived from green-husked walnut with clotrimazole against Candida albicans in female rats. Methods: In this study, 35 female Wistar rats were randomly assigned to 5 groups. A total of 4 groups of rats were infected vaginally with C. albicans and 1 group was not infected (negative control). The 4 infected groups received the following treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…Black walnut or Juglans nigra ( J. nigra ) is a deciduous tree that is known as the eastern black walnut. This tree is indigenous to eastern North America, where it is grown in places such as South Dakota in the United States [82]. The detachment of its fruit takes place around October, consisting of a husk, a hard shell, and a kernel.…”
Section: Walnutsmentioning
confidence: 99%
See 1 more Smart Citation
“…Black walnut or Juglans nigra ( J. nigra ) is a deciduous tree that is known as the eastern black walnut. This tree is indigenous to eastern North America, where it is grown in places such as South Dakota in the United States [82]. The detachment of its fruit takes place around October, consisting of a husk, a hard shell, and a kernel.…”
Section: Walnutsmentioning
confidence: 99%
“…Abedi et al [82] investigated the effects of extracts obtained from black walnut green husk and clotrimazole on Candida albicans ( C. albicans ) in female rats. Their obtained results demonstrated that the growth of C. albicans was significantly inhibited in female rats that had been treated for one week with the prepared vaginal creams, which contained 4% of J. nigra extract, and had a similar effect to clotrimazole.…”
Section: Walnut Husk Usesmentioning
confidence: 99%
“…Two estradiol valerate doses were injected subcutaneously in the lower abdomen during the first and third days to suppress the rats’ hormonal systems. 4 After the second estradiol injection, 0.1 mL yeast suspension was injected into the vagina, and the rats were kept upside down for about 1 minute to ensure the inoculum.…”
Section: Methodsmentioning
confidence: 99%
“… 2 Previous investigations revealed that in different provinces of Iran, the frequency of VVC varies from 4.8% to 73%. 3 - 6 Although it is not a life-threatening condition, it can cause physical and psychological problems and deteriorate marital relationships. 1 The limited number of effective antifungal drugs is an excellent issue in treating fungal infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation